Strategic Management of the Socially Responsible Firm: Integrating Management and Marketing Theory - Murray, Keith B.; Montanari, John B. (Academy of Management Review, 1986)
Keith B. Murray, John R. Montanari, Strategic Management of the Socially Responsible Firm: Integrating Management and Marketing Theory, The Academy of Management Review, Vol. 11, No. 4 (Oct., 1986), pp. 815-827